RNA Decay and RNA Silencing in Plants: Competition or Collaboration? - Christie, Michael; Brosnan, Christopher A.; Rothnagel, Joseph A.; Carroll, Bernard J. (Frontiers in Plant Science, 2011)
Initiation of RNA polymerase II transcription signals the beginning of a series of physically and functionally coupled pre-mRNA processing events that transform an RNA transcript into a highly structured, mature ribonucleoprotein complex. With such a complexity of co-transcriptional processes comes the need to identify and degrade improperly processed transcripts. Quality control of mRNA expression primarily involves exonucleolytic degradation of aberrant RNAs. RNA silencing, on the other hand, tends to be viewed separately as a pathway that primarily functions in regulating endogenous gene expression and in genome defence against transposons and viruses. Here, we review current knowledge of these pathways as they exist in plants and draw parallels to similar pathways in other eukaryotes. We then highlight an unexplored cross-talk and interdependence that exists between the RNA silencing and RNA decay pathways of plants. Interdependence is evidenced by their shared genetic requirements, while cross-talk is necessitated by their competition for RNA substrates.